ASHRAE Global Thermal Comfort Database II: Thermal Comfort of Mechanically Ventilated and Naturally Ventilated Office Building - Mahat, Nur Muhammad Aidil; Hariri, Azian (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Optimum thermal comfort is vital in office building for work performance improvement. The objective of this research is to determine the relationship between thermal comfort parameters with PMV index value in naturally ventilated and mechanically ventilated office building in tropical wet Savanna (India) and winter Mediterranean climates (United Kingdom). The data is retrieved from the ASHRAE global thermal comfort database II and had been analyzed by SPSS analysis software. Total of 160 samples were retrieved and tested for the normality of the data, correlation between thermal comfort parameters with PMV index value and linear regression analysis. Air temperature, relative humidity, air velocity and clothing insulation are the parameters that shows significantly correlate with PMV index value. The difference between naturally ventilated office in India and United Kingdom in optimum thermal comfort temperature is 3.11℃ while for mechanically ventilated office, the difference optimum thermal comfort temperature is 3.42℃. The optimum thermal comfort temperature between mechanically ventilated and naturally ventilated office in India and United Kingdom are almost similar. In conclusion, different thermal comfort parameters have different significant to the PMV index value in different climates.